1970
DOI: 10.1063/1.1653177
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Formation in Co2 Lasers

Abstract: The rate of CO2 dissociation in a flowing CO2 laser discharge has been measured. This rate is consistent with published cross sections for direct electron impact dissociation when averaged over the appropriate electron energy distribution. The dissociation process in the flowing gas discharge is found to result in an axial variation of plasma properties and of the laser medium. Implications of the CO variation for many conventionally operated CO2 lasers are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Different authors use different cross sections to estimate the dissociation rate coefficient. The 7 eV excitation cross section from Phelps [75,187], as used by [203][204][205], seems to lead to a reasonable calculation of CO 2 dissociation in various conditions [88,202]. However, in a recent experimental study [89] Morillo-Candas et al have shown that electron impact dissociation of CO 2 is very well described in the range E/N ∈ (45, 105) Td by the cross sections calculated by Polak and Slovetsky [206], while the Phelps 7 eV cross section leads to an overestimation of the dissociation rate coefficient.…”
Section: Comentioning
confidence: 99%
“…Different authors use different cross sections to estimate the dissociation rate coefficient. The 7 eV excitation cross section from Phelps [75,187], as used by [203][204][205], seems to lead to a reasonable calculation of CO 2 dissociation in various conditions [88,202]. However, in a recent experimental study [89] Morillo-Candas et al have shown that electron impact dissociation of CO 2 is very well described in the range E/N ∈ (45, 105) Td by the cross sections calculated by Polak and Slovetsky [206], while the Phelps 7 eV cross section leads to an overestimation of the dissociation rate coefficient.…”
Section: Comentioning
confidence: 99%
“…This linearity provides experimental evidence of the validity of the assumptions underlying the used method for the determination of the CO concentration. A detailed description of the method can be found in [2].…”
Section: Methodsmentioning
confidence: 99%
“…for lower E/N). Since the variations of the reduced electric field strength E/N with discharge current are very small, the changes in CO 2 dissociation are due to changes in the electron density and in the rate of the regeneration processes (reactions (2) and (3)). On the one hand, the electron density and hence the production of CO molecules by electron impact increases with discharge current.…”
Section: Steady-state Co 2 Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that CO 2 molecule dissociates in an electric discharge leading to the formation of CO and O 2 in the CO 2 laser gain medium and the extent of CO formation has been measured experimentally by many researchers in the past [14,15]. The discharge conditions, along with flow rate, gas composition etc, influence the dissociation.…”
Section: Introductionmentioning
confidence: 99%